Urological approach for cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in a clinical care center. Issue 6 (2nd November 2018) - Trujillo, Carlos Gustavo; Domínguez, Cristina; Robledo, Daniela; Caicedo, Juan Ignacio; Bravo-Balado, Alejandra; Cataño, Juan Guillermo; Cortés, Natalia; Parra, Lina; Riaño, Wilson; Londoño-Schimmer, Eduardo; Otero, Jorge; Herrera, Gabriel; et al.
Abstract: Background: Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is associated with significant manipulation of the urinary tract (UT). We aim to describe the urological events and their management in patients who underwent CRS-HIPEC. Methods: Clinical records of patients who underwent treatment between 2007 and 2015 were reviewed. Urological events and their multidisciplinary management were analyzed. Descriptive statistics were calculated. Results: A total of 103 patients were included. Mean age was 51 years (SD ± 11.8). Mean peritoneal cancer index (PCI) was 20.4 (SD ± 10.1). Primary tumors included appendicular (64%), gynecological (16%), colorectal (10%), and peritoneal mesotheliomas (9%). Ninety-three percent of patients had bilateral ureteral catheters inserted prior to surgery, without complications. Intraoperative UT injuries occurred in 7% of patients. In 5% of patients, tumor invasion of the bladder was evident at surgery and partial resection and primary repair of the bladder wall was performed. Urological complications included urinary tract infection (UTI) (21%) acute post-renal failure (4%), urinary fistulae (4%), and acute urinary retention (AUR) (1%). Conclusions: In our study, intraoperative UT events and postoperative complications, although not neglectable, were infrequent. Due to the high complexity of these cases, a multidisciplinary approach is mandatory. However, randomized clinical trials are necessary to clarify current data on the need and efficacy of prophylactic ureteral catheterization in patients undergoing CRS-HIPEC.